Changes of Syntactic Patterns in the Textual Tradition of the Book of Isaiah: A Corpus-Linguistic Approach - Oosting, Reinoud (HIPHIL Novum, 2017)
Assuming that biblical texts have been reworked and updated during the long period of their history of development and transmission, this paper examines the syntactic changes in the textual tradition of the Book of Isaiah. The first part is devoted to the linguistic variation within the authoritative text of Isaiah and concentrates on the interchange of prepositions in the Masoretic Text. The second part deals with the transmission of the text of Isaiah and pays attention to the differences between the Masoretic Text of Isaiah and the text of Isaiah in the Dead Sea scrolls and the Old Greek Translation, the Septuagint. In both parts, the linguistic patterns gathered from the ETCBC database serve as the starting point for the examination. By computer-assisted registering, sorting, and comparing the various syntactic patterns, one gains insight into the complex history of the Hebrew text of Isaiah.